Agriculture's 'other' contingent labour source. Agricultural contractors and relationships of interdependence at the farmer-contractor interface. (August 2020) - Nye, Caroline
Abstract: The decline in traditional farm labour since the advent of industrialisation is undeniable. Despite this, the increasing contribution of agricultural contractors to labour on British farms has been almost entirely ignored by the research agenda. Neither employed as 'traditional' farm workers, nor as seasonal workers generally considered to possess minimal agency in farmer-worker interactions, the agricultural contractor has become a principal actor in the supply of contingent labour in agriculture. Using qualitative data from 28 semi-structured interviews with farmers and contractors in Devon, this paper examines contemporary relationships of interdependence between farmers and contractors from a relational perspective. It contributes to theories of organisational behaviour in the agricultural workplace by reassessing the idea that labour flexibility in agriculture always adheres to the needs of the firm, revealing instead a new conceptual model of interdependence between the agricultural contractor and the farmer. Highlights: The agricultural labour market has continued to move to one of increased flexibility. Agricultural contractors are crucial to the efficiency of the industry. Relationships of attached and detached interdependence are revealed between farmers and contractors. Various agents impact upon detached and attached interdependent relationships making them susceptible to change.